Investigation of Surface Roughness and Tool Wear Length With Varying Combination of Depth of Cut and Feed Rate of Aluminium Alloy and P20 Steel Machining - Madan Varmma, Suparmaniam; A. R., Yusoff (IOP Publishing, 2016)
High-speed milling technique is often used in many industries to boost productivity of the manufacturing of high-technology components. The occurrence of wear highly limits the efficiency and accuracy of high- speed milling operations. In this paper, analysis of high-speed milling process parameters such as material removal rate, cutting speed, feed rate and depth of cut carried out by implemented to conventional milling. This experiment investigate the effects of varying combination of depth of cut and feed rate to tool wear rate length using metallurgical microscope and surface roughness using portable surface roughness tester after end milling of Aluminium and P20 steel. Results showed that feed rate significantly influences the surface roughness value while depth of cut does not as the surface roughness value keep increasing with the increase of feed rate and decreasing depth of cut. Whereas, tool wear rate almost remain unchanged indicates that material removal rate strongly contribute the wear rate. It believe that with no significant tool wear rate the results of this experiment are useful by showing that HSM technique is possible to be applied in conventional machine with extra benefits of high productivity, eliminating semi-finishing operation and reducing tool load for finishing.